Clay-Based Pharmaceutical Formulations and Drug Delivery Systems - Viseras, César (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes recent advances in the use of clays in the design of medicinal products and medicinal devices. The pharmaceutical applications of nanoclays are far ranging, because of their distinct advantages: they are versatile (possess a wide range of mechanical, chemical and physical properties) and available at reasonable costs. Some special clays (mainly kaolinite, halloysite, montmorillonite, saponite, hectorite, palygorskite and sepiolite), as well as semi-synthetic (organoclays) or synthetic (double layer hydroxides) derivatives, are very useful materials for modulating drug delivery. In the last decade, several actives have been loaded onto nanoclays and similar inorganic excipients to increase solubility, improve stability, reduce toxicity, and enhance bioavailability, with a consequent increase in therapeutic response. Polymer/clay nanocomposites with synergic properties have been developed, showing improved mechanical properties with respect to the pristine polymer matrices and allowing modified release of loaded actives. Moreover, nanoclays have very recently demonstrated positive effects on the proliferation and migration of fibroblasts. The development of clay-based medicinal products and medicinal devices requires experience in the fields of both clay structure and properties and pharmaceutical technology design.